The Value of Islamic Teaching and Sundanese Culture in The Ruwatan Leuweung Babakti Mandala Manglayang - Deni Miharja; Sigit Fitro Prasetyo (Religio: Jurnal Studi Agama-agama, 2021)
Generated by the ancestor, the tradition of Ruwatan Leuweung Babakti Mandala Manglayang in Bandung is still preserved today. The ceremony is such an expression of social trust to maintain and keep Leuweung Babakti Mandala Manglayang which includes some values of Islamic teachings and Sundanese culture. This study aimed to discuss three points. First is the ceremonial system. Second, to determine the belief system contained in the Ruwatan Leuweung Babakti Mandala Manglayang tradition. Third, to examine the influence of Islamic teachings and Sundanese culture in the Ruwatan Leuweung Babakti Mandala Manglayang tradition. This study uses qualitative methods, namely field research using data collection techniques through observation, interviews, and documentation. It discusses the system of ceremonies, beliefs, and the influence of Islamic teachings and Sundanese culture in the Ruwatan Leuweung Babakti Mandala Manglayang Tradition. The research concludes that the Ruwatan tradition is a system of religious ceremonies that are carried out annually. It is carried out solemnly by all members of the community.